BIOFUEL FOR NATURE PROTECTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Energy sector has been one o f the most important priorities since reestablishment o f the independence o f Latvia. The deficiency o f energy resources in Latvia has created a need to assess all the possibilities to utilize all the local enrgy resources, including the biological ones, to motivate the trends in the development of energetics in Latvia. Therefore data have been collected, calculations made and possibilities analysed to replace the imported energy resources. From the renewable energy in Latvia there are used the wind, solar, hydraulic and bioenergy. A biofuel programme has been worked out in Latvia. It is envisaged to develop the production of ethanol and rape oil for vehicle engines. For this purpose an arable area of 288 thousand ha is needed. A huge non-utilised reserve in Latvia is methane fermentation of organic agricultural and municipal residue and sewage from food industry. It is calculated that about 170 million m3 biogas can be obtained in Latvia. Implementation of the fuel programme will stimulate Latvia’s economy.